Pengaruh Pembiayaan Lembaga Keuangan Mikro Syariah, Inflasi Dan Suku Bunga Terhadap Pertumbuhan Ekonomi Di Indonesia Tahun 2016-2020 - Ahmad Fauzul Hakim Hasibuan; Muhammad Roni; Putri Fajar (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2022)
This study examined the effect of Islamic Microfinance Institutions Financing, Inflation, and Interest Rates on Economic Growth during 2016-2020. This study used secondary data taken from the official website of the financial services authority (OJK) with monthly data from January 2016 to December 2020. This quantitative study used VAR (Vector Auto Regression) analysis supported by stationary test, optimal lag test, VAR model stability test, Granger causality test, cointegration test, impulse response function test, and variance decomposition test. The results showed that interest was more dominant in influencing the economic growth of Indonesia in the short and long term, and Granger causality test results showed that all variables had a causal relationship with each other, meaning that each variable had a two-way relationship with the other variables. Future researchers should use more approaches, not only Islamic Microfinance Institutions Financing, Inflation and Interest rates but also income, inclusion, PKR financing, and investment as a determinant of the rate of economic growth in Indonesia.